The Arianna thread: the matching of S-100 family with the RyR’s muscle receptor - Giorgio Fano Illic; Stefania Fulle; Silvia Belia (European Journal of Translational Myology, 2020)
The functional state of RyR depends on the intracellular calcium concentration and on the oxidation state of its protein components in some particular sites and of some sentinel amino acids. In addition to the regulation of the RyR channel by exogenous substances (caffeine, ryanodine), ions environmental situations (oxidative state), other components, such as some endogenous proteins present in the sarcoplasm and/or and muscle membranes are able to determine changes in the Ca2+ channel activity. Among these, calmodulin and S-100A could determine the modification of channel status in the skeletal muscle. The currently available data can be justified if one uses a simplified S-100/CaM and RyR interaction model for the regulation of Ca2+ release in skeletal muscle. Under resting conditions, the CaM/S100A1 binding domain on RyR1 is predominantly dependent on S100A1. Vice versa when the intracellular Ca2+ concentration becomes high as well as during repetitive (tetanus) stimulation, the Ca-CaM bond becomes dominant, shifting S100A1 from RyR1 and promoting channel inactivation.